GAMBARAN PSIKOEDUKASI TERHADAP KELUARGA PENDERITA SKIZOFRENIA - Stefani Virlia (Universitas Bunda Mulia, 2014)
The process of recovery of people with schizophrenia in Indonesia are still poor. This is because the recovery process is long and time consuming need social support from family. A patient who has been getting medicine and good care at the hospital could have returned relapse if there‟s no support of his/her family. Support from family is also affected how much information they can understand about the disorder sufferers so that families can be more accepting of patient. This study aims to determine how the image of the family psychoeducation in patients with schizophrenia. This study used a qualitative approach to the 2 families of patients. Data was collected through interviews and observation techniques and the results were analyzed using content analysis. The result of this research is the process of psychoeducation to families of people with schizophrenia could be successful when an awareness and sensitivity on the part of the family of the condition of the patient so that the patient can return to optimal function. Keywords: patient with schizopherenia, family, psychoeducation